Cultura de devoção: um estudo sobre os processos de legitimação e de manutenção e os motivos da devoção a uma organização - Vargas, Katiuscia de Fátima Schiemer (2018)
The present study aims to understand how the legitimization and maintenance processes of the devotion culture occur and their interlacing with the reasons why the workers become devotees to an organization. In this sense, were defined the following specific objectives: a) to describe the cultural context of the studied organization emphasizing the elements that compose and characterize the devotion culture; b) characterize the mediation processes (economic, political, ideological and psychological) invested by the organization and the forms of power embodied in them; c) analyze the reasons why workers become devotees to the organization. For that, an exploratory research of qualitative approach was developed, starting from a case study in a company of the Information Technology and Statistical Intelligence field, denominated fictitiously of Confidence, chosen for being representative of the devotion culture phenomenon. The research data were collected by means of open interviews - initial field approximation -, semi-structured interviews - data collection itself -, discursive sources that composed the analytical corpus and direct observations throughout the field immersion. Thirty workers, 10 (ten) of the "management" organizational level and 20 (twenty) of the "operation" were taken as research subjects. As analytical lens, was used the Sociological Discourse Analysis (SDA), linked to the Spanish Tradition of Qualitative Social Research. Concerning to the research results, it was observed a cultural context composed by a concrete plan (scenarios, practices and organizational strategies) and a subjective plan (significations), endowed of symbolisms repeatedly propagated, representing and reverberating the philosophy that the company wants to institute and making possible the institutionalization of an infrastructure of maintenance of the devotion culture. In what referes to the mediation processes, a multidimensional network was characterized, encompassing the economic, political, ideological and psychological spheres of mediation, which has embodied in itself a symbolic and perlocutionary power. Adding to the cultural context and the mediation processes, the meanings of work in its individual, organizational and social dimensions were also presented as reasons for the devotion of workers to the organization. From these results, it was verified that the core of the devotion culture resides in the ideology and the psychological alienation, being both agents of legitimation and maintenance. Ideology is a foundation, at the same time that it is systematizer and reinforcer of the devotion culture; the psychological alienation, in turn, supports the ideology, ensuring the affective, emotional and symbolic domain of the workers and representing the rooting of the devotion culture. The cultural context and disseminated symbolisms, the economic and political mediation processes and the meanings of labor contribute in a subsidiary way to the legitimation and maintenance of the devotion culture. In conclusion, the legitimation and maintenance processes are interconnected, occur simultaneously and feed back itself so that the reality of the devotion culture be perceived as valid and plausible and, above all, sustains itself over time.